2007
DOI: 10.2343/geochemj.41.323
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of fluorescent dissolved organic matter in river waters

Abstract: Photodegradation of dissolved organic matter (DOM), collected from two upstream and one downstream sites in the Lake Biwa watershed in Japan, was investigated using fluorescence properties of three-dimensional excitation emission matrix (3-D EEM). Solar irradiation caused a decrease in the dissolved organic carbon (DOC) concentration and in the fluorescence peak intensity (FI) of fulvic acid (FA)-and protein-like substances in DOM. Mineralization of DOC during an irradiation period (13 days) was observed to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 31 publications
7
44
2
3
Order By: Relevance
“…It has been demonstrated that photoirradiation reduces the fluorescence intensity by decomposing fulvic and humic acids (Moran et al, 2000;Wu et al, 2005), tryptophan-like component (Moran et al, 2000;Mostofa et al, 2007b), and FWAs or household detergents (Poiger et al, 1999;Mostofa et al, 2005aMostofa et al, , 2010 in natural waters. On the other hand, microbial degradation has been observed to either enhance or decrease the fluorescence intensity in natural waters.…”
Section: (Continued)mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that photoirradiation reduces the fluorescence intensity by decomposing fulvic and humic acids (Moran et al, 2000;Wu et al, 2005), tryptophan-like component (Moran et al, 2000;Mostofa et al, 2007b), and FWAs or household detergents (Poiger et al, 1999;Mostofa et al, 2005aMostofa et al, , 2010 in natural waters. On the other hand, microbial degradation has been observed to either enhance or decrease the fluorescence intensity in natural waters.…”
Section: (Continued)mentioning
confidence: 99%
“…On the other hand, microbial degradation has been observed to either enhance or decrease the fluorescence intensity in natural waters. This is mainly the consequence of the complex interactions between micro-organisms and fulvic and humic acids (Moran et al, 2000;Ma and Green, 2004;Mostofa et al, 2007a), detergent components (Table 1) and tryptophan-like compounds (Moran et al, 2000;Baker and Inverarity, 2004;Mostofa et al, 2007b; Table 1). The photochemical and microbial processing of FDOM yields a variety of photo-and microbial transformation intermediates in natural waters (Amador et al, 1989;Allard et al, 1994;Amon and Benner, 1996;Kramer et al, 1996;Ma and Green, 2004; Table 1 and references therein).…”
Section: (Continued)mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite very different mechanisms involved, microbial processes have several analogies with photochemical ones as far as the final products are concerned (Köhler et al, 2002;Ma and Green, 2004;Millero, 2007;Moran et al, 2000;Mostofa et al, 2007;Mostofa and Sakugawa, 2009;Zhang et al, 2009;Letscher et al, 2013;Mostofa et al, 2011Mostofa et al, , 2013bMostofa et al, , 2013d The compounds formed from DOM and POM because of photochemical and microbial processes would be substantially increased due to increased temperature following global warming. These compounds act as nutrients, enhancing photosynthesis and, as a consequence, primary production as summarized in earlier reports ( Fig.…”
Section: Algal Toxins or Red Tide Toxinsmentioning
confidence: 99%
“…A number of papers have been published on the direct photolysis of chemicals in water using the Hg-lamp (K. G. Mostafa, 2007, J.P. Escalanda, 2008, S.T. Ong, 2009).…”
Section: Introductionmentioning
confidence: 99%